Glycated haemoglobin A1c compared to fasting plasma glucose and oral glucose tolerance testing for diagnosing type 2 diabetes and pre-diabetes : a meta-analysis - Rheeder, Paul (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.